Work-family conflict and depressive complaints among Dutch employees: examining reciprocal associations in a longitudinal study - Yoy Bergs; Huub Hoofs; IJmert Kant; Jos Slangen; Nicole WH Jansen (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: The aim of this study was to examine the reciprocal association between work-family conflict and depressive complaints over time. METHODS: Cross-lagged structural equation modeling (SEM) was used and three-wave follow-up data from the Maastricht Cohort Study with six years of follow-up [2416 men and 585 women at T1 (2008)]. Work-family conflict was operationalized by distinguishing both work-home interference and home-work interference, as assessed with two subscales of the Survey Work-Home Interference Nijmegen. Depressive complaints were assessed with a subscale of the Hospital Anxiety and Depression scale. RESULTS: The results showed a positive cross-lagged relation between home-work interference and depressive complaints. The results of the χ^2 difference test indicated that the model with cross-lagged reciprocal relationships resulted in a significantly better fit to the data compared to the causal (Δχ^2 (2)=9.89, P=0.001), reversed causation model (Δχ^2 (2)=9.25, P=0.01), and the starting model (Δχ^2 (4)=16.34, P=0.002). For work-home interference and depressive complaints, the starting model with no cross-lagged associations over time had the best fit to the empirical data. CONCLUSIONS: The findings suggest a reciprocal association between home-work interference and depressive complaints since the concepts appear to affect each other mutually across time. This highlights the importance of targeting modifiable risk factors in the etiology of both home-work interference and depressive complaints when designing preventive measures since the two concepts may potentiate each other over time.